Meteorological conditions, seasonal and annual mass balances of Chhota Shigri Glacier, western Himalaya, India. Issue 71 (January 2016) - Azam, Mohd Farooq; Ramanathan, AL.; Wagnon, P.; Vincent, C.; Linda, A.; Berthier, E.; Sharma, P.; Mandal, A.; Angchuk, T.; Singh, V.B.; Pottakkal, J.G.
Abstract: We present the updated glaciological mass balance (MB) of Chhota Shigri Glacier, the longest continuous annual MB record in the Hindu-Kush Karakoram Himalaya (HKH) region. Additionally, 4 years of seasonal MBs are presented and analyzed using the data acquired at an automatic weather station (AWS-M) installed in 2009 on a lateral moraine (4863ma.s.l.). The glaciological MB series since 2002 is first recalculated using an updated glacier hypsometry and then validated against geodetic MB derived from satellite stereo-imagery between 2005 (SPOT5) and 2014 (Pléiades). Chhota Shigri Glacier lost mass between 2002 and 2014 with a cumulative glaciological MB of –6.72mw.e. corresponding to a mean annual glacier-wide MB (Ba ) of –0.56mw.e. a –1 . Equilibrium-line altitude (ELA0 ) for the steady-state condition is calculated as ~4950ma.s.l., corresponding to an accumulation–area ratio (AAR0 ) of ~61%. Analysis of seasonal MBs between 2009 and 2013 with air temperature from AWS-M and precipitation from the nearest meteorological station at Bhuntar (1050ma.s.l.) suggests that the summer monsoon is the key season driving the interannual variability of Ba for this glacier. The intensity of summer snowfall events controls the Ba evolution via controlling summer glacier-wide MB (Bs ).